TANTANGAN LEMBAGA PENDIDIKAN DI TENGAH PERSAINGAN GLOBAL - Bani, Suddin (Inspiratif Pendidikan, 2016)
Efforts to promote education should ideally be realized jointly between the government, community, business world in improving education institutions to set up a more skilled labor force, and so forth. Such efforts must be done comprehensively started the primary level up to tertiary education. One of them the government should do is to make improvements in the areas of curriculum. Government in order to homogenize step in revamping the education issue has redefined the concept of the curriculum is a set of plans and arrangements regarding the objectives, content and learning materials, as well as the means used to guide the implementation of learning activities to achieve specific educational objectives.